Analisis Kebutuhan Air Irigasi Menggunakan Aplikasi Software Cropwat Daerah Irigasi Palioi Kindang Kabupaten Bulukumba - Wiradinata, Nurdiansyah; Badrun, Burhanuddin; Cangara, Satriawati (Program Studi Teknik Sipil Universitas Bosowa, 2024)
The Palioi irrigation area, Bulukumba Regency, has a land area of 23.51 Ha with the main water source being the Bangsalayya Weir which is located in Borong Rappoa Bulukumba village, due to land conversion causing the irrigation channels in this area to be less than optimal. The aim of this research is to review Palioi's irrigation water needs. Calculations were carried out using the Cropwat software application version 8.0. This application is very helpful in managing data so that it produces data that can be used. The need for irrigation water starts from the beginning of April using a planting pattern for secondary crops, rice and secondary crops. The results of this research show that the existing irrigation water discharge is 4.41 m³/deck, with an irrigated land area of 23.51 Ha, whereas by using the Cropwat Software Application the irrigation water discharge is 3.84 m³/deck, with The area of land that is irrigated is 23.51 Ha. The results of this research show that with land conversion, the existing availability of irrigation water is still sufficient for irrigation water needs for DI Palioi